Penggunaan Media Video Karikatur Untuk Meningkatkan Kesadaran Remaja Tentang Bahaya Anemia pada Kehamilan di Usia Dini di SMP Karya Ruteng - Febriani Jeramat, Alexandra; Suryani , Ambrosia; Lindang, Evarista; Nanur, Familia Esriani; Tini, Atanasia Trian; Sunarti, Eufrasia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Adolescence is a time of transition, growth, exploration, and opportunity. Teenage pregnancy means that teenagers who are married or unmarried are likely to get pregnant at a relatively young age under 20 years of age. The impact of high-risk pregnancies on teenagers is such as miscarriage, preterm delivery, easy infection, pregnancy poisoning and high maternal mortality. This situation is caused by the immaturity of the reproductive organs for pregnancy, so it can be detrimental to the mother's health, development and growth of the fetus. The aim of this community service is to increase teenagers' knowledge regarding the dangers of anemia in early pregnancy. The method used in this community service is literature review and qualitative descriptive with data collection techniques using pre-test and post-test questionn.The results of community service aimed at teenagers have increased knowledge regarding the dangers of anemia in early pregnancy.